A TEST OF THE OBLIQUE-RIFTING MODEL FOR TRANSFER ZONE DEFORMATION IN THE NORTHERN FEN-WEI RIFT: IMPLICATIONS FROM THE 1989 M 6.1 DATONG-YANGGAO EARTHQUAKE SWARM - Yan-Qun Zhuo; Yanshuang Guo; S. A. Bornyakov; Jin Ma (Геодинамика и тектонофизика)
Tectonophysical experiments show that the evolution of the Fen-Wei Rift is controlled by oblique rifting. A key characteristic of the model in our study is that the western and eastern borders of the transfer zone between the adjacent NEE-striking extensional basins tend to form right-lateral strike-slip faults with slight normal slip as a result of the interaction between the adjacent NEE-striking extensional basins under oblique rifting. The current deformation of the Fen-Wei Rift can be clarified by testing this predicted deformation characteristic. Our analysis of the relocation and focal mechanism solutions of the 1989 M 6.1 Datong-Yanggao earthquake swarm, which was the largest earthquake that occurred in the Fen-Wei Rift in the last 200 years, suggests that the transfer zone between the Yangyuan and Hunyuan basins is bounded by the NNE-striking right-lateral strike-slip faults with slight normal slip at its eastern and western edges. This consistency between the model and the current tectonic activity in the study area indicates that oblique rifting still plays an important role in the current deformation of the northern Fen-Wei Rift.